Prophetic-Humanization Communication among Generation Z on COVID-19 Information - Hak, Ade Abdul; Rianti, Fahma; Irfaniah, Hikmah (Program Studi Ilmu Perpustakaan UIN Alauddin, 2023)
For Generation Z, especially those who study librarianship in the digital age, e-literacy is essential. It refers to using a computer with information, media, moral literacy, and learning and thinking abilities. One of them is how they communicate COVID-19 information. Through the behavior of librarianship students from the seven State Islamic Universities in Indonesia, this study aims to measure the impact of e-literacy on prophetic-humanization communication among Generation Z. With a 9% error rate and a sample size of 116 pupils, stratified random sampling (proportional) was used to acquire the data. The findings strongly correlate information usage behavior, prophetic-humanization communication, and e-literacy. In addition, e-literacy impacts prophetic communication by changing how people use COVID-19 data. Only the level of learning and thinking abilities can fully demonstrate the good and significant impact of e-literacy skills through information behavior on humanization-prophetic communication. This study's relevance is that students should increase their e-literacy to communicate more prophetically and ethically using electronic media.